ORGANIZATIONAL STRUCTURES, COMPARATIVE ANALYSIS AND THE NEED FOR THEIR EXISTENCE (Isagoge - Journal of Humanities and Social Sciences, 2023)
Organizations need to organize themselves in order to achieve success. A current theme such as organizational structures needs regular studies in order to never be outdated, so this article adds to its importance. The purpose of this paper is to study the main styles of organizational structure, through a literature review, promoting practical examples of the issue whenever possible. This brings to the literature a new vision of the theme, something that can be very useful to the various organizations that want to x-ray their way of acting. The lack of studies in portuguese also gives this study greater importance. It is concluded that the existence of structure is essential, however the choice of the best structure depends a lot on the way of acting, as well as on the objectives of the organization itself.
Keywords: Organizational Structures; Organization; Efficiency